Kinematic and kinetic comparison of baseball pitching among various levels of development - Glenn, G. S.; Fleisig, S.; Barrentine, S. W.; Zheng, N.; Escamilla, R. F.; Andrews, J. R. (Journal of Biomechanics, 1999)
Proper biomechanics help baseball pitchers minimize their risk of injury and maximize performance. However previous studies involved adult pitchers only. In this study, 23 youth, 33 high school, 115 college, and 60 professional baseball pitchers were analyzed. Sixteen kinematic (11 position and five velocity), eight kinetic, and six temporal parameters were calculated and compared among the four levels of competition. Only one of the 11 kinematic position parameters showed significant differences among the four levels, while all five velocity parameters showed significant differences. All eight kinetic parameters increased significantly with competition level. None of the six temporal parameters showed significant differences. Since 16 of the 17 position and temporal parameters showed no significant differences, this study supports the philosophy that a child should be taught `proper' pitching mechanics for use throughout a career. Kinetic differences observed suggest greater injury risk at higher competition levels. Since adult pitchers did not demonstrate different position or temporal patterns than younger pitchers, increases in joint forces and torques were most likely due to increased strength and muscle mass in the higher level athlete. The greater shoulder and elbow angular velocities produced by high-level pitchers were most likely due to the greater torques they generated during the arm cocking and acceleration phases. The combination of more arm angular velocity and a longer arm resulted in greater linear ball velocity for the higher level pitcher. Thus, it appears that the natural progression for successful pitching is to learn proper mechanics as early as possible, and build strength as the body matures.